Reducing oil absorption in pea starch through two-step annealing with varying temperatures - Xie, Shumin; Li, Zihan; Duan, Qingfei; Huang, Weijuan; Huang, Wei; Deng, Yawei; Chen, Pei; Xie, Fengwei (Food hydrocolloids, 2024)
In this study, we investigated the effects of one-step and two-step annealing on pea starch (PS) and their impact on the starch structure and oil absorption following frying. Compared to native PS, both one-step and two-step annealing treatments significantly reduced starch solubility, swelling power, oil absorption, and specific surface area while increasing water absorption. The extent of these changes depended on the specific annealing parameters applied. Notably, among all the starch samples, PS-45-55-F (PS subject to two-step annealing at 45 °C and then 55 °C, followed by frying) exhibited the lowest oil absorption. Scanning electron microscopy (SEM) results revealed that PS-45-F (PS subject to one-step annealing at 45 °C, followed by frying) and PS-45-55-F retained more of the original starch structure after frying. Analytical techniques including X-ray diffraction (XRD), Fourier-transform infrared (FT-IR), and differential scanning calorimetry (DSC) consistently indicate that two-step annealed starch (PS-45-55-F) better preserved both long-range and short-range ordered structure of starch granules during frying. Additionally, it enhanced the thermostability of annealed starch, making it more effective in inhibiting oil absorption. These findings highlight the potential of two-step annealed starch for the development of low-oil, high-quality, and healthy fried or pre-fried food products, such as coated fried chicken and tempura. [Display omitted] •Two-step annealing significantly affected the rearrangement and optimization of starch molecules.•The oil content of two-step annealed pea starch exhibited the lowest value.•SEM results revealed that two-step annealed starch substantially retained the original morphology following frying.•Two-step annealed starch better preserved both long-range and short-range ordered structure of starch granules during frying.